Does relative age affect speed and quality of transition from school to work? - Luca Fumarco; Alessandro Vandromme; Levi Halewyck; Eline Moens; Stijn Baert (Global Labor Organization (GLO), 2022)
We are the first to estimate the impact of relative age (i.e., the difference in classmates' ages) on both speed and quality of individuals' transition from education to the labour market. Moreover, we are the first to explore whether and how this impact passes through characteristics of students' educational career. We use rich data pertaining to schooling and to labour market outcomes one year after graduation to conduct instrumental variables analyses. We find that a one-year increase in relative age increases the likelihood of (i) being employed then by 3.5 percentage points, (ii) having a permanent contract by 5.1 percentage points, and (iii) having full-time employment by 6.5 percentage points. These relative age effects are partly mediated by intermediate outcomes such as having had a schooling delay at the age of sixteen or taking on student jobs. The final mediator is particularly notable as no earlier studies examined relative age effects on student employment.We are the first to estimate the impact of relative age (i.e., the difference in classmates' ages) on both speed and quality of individuals' transition from education to the labour market. Moreover, we are the first to explore whether and how this impact passes through characteristics of students' educational career. We use rich data pertaining to schooling and to labour market outcomes one year after graduation to conduct instrumental variables analyses. We find that a one-year increase in relative age increases the likelihood of (i) being employed then by 3.5 percentage points, (ii) having a permanent contract by 5.1 percentage points, and (iii) having full-time employment by 6.5 percentage points. These relative age effects are partly mediated by intermediate outcomes such as having had a schooling delay at the age of sixteen or taking on student jobs. The final mediator is particularly notable as no earlier studies examined relative age effects on student employment.
Keywords: I21; J23; J24; J6; 330; relative age; school starting age; labour market transition